Mucus production and chronic obstructive pulmonary disease, a possible treatment target: zooming in on N-acetylcysteine - Federico Baraldi; Tommaso Bigoni; Maria Pia Foschino Barbaro; Claudio Micheletto; Giulia Scioscia; Alessandro Vatrella; Alberto Papi (Monaldi Archives for Chest Disease)
Mucus hypersecretion is a trait of chronic obstructive pulmonary disease (COPD) associated with poorer outcomes. As it may be present before airway obstruction, its early treatment may have a preventive role. This narrative review of the literature presents the role of mucus dysfunction in COPD, its pathophysiology, and the rationale for the use of N-acetylcysteine (NAC). NAC can modify mucus rheology, improving clearance and reducing damage induced MUC5AC expression. It exerts a direct and indirect (glutathione replenishment) antioxidant mechanism; it interferes with inflammatory molecular pathways, including inhibition of nuclear factor-kB activation in epithelial airway cells and reduction in the expression of cytokine tumor necrosis factor α, interleukin (IL)-6, and IL-10. Some clinical experiences suggest that the adjunctive use of NAC may reduce symptoms and improve outcomes for patients with COPD. In conclusion, NAC may be a candidate drug for the early treatment of subjects at risk of COPD development.